Assessment of the efficacies of correction procedures for multiple thin layer effects on Cone Penetration Tests. Issue 144 (May 2021) - Yost, Kaleigh M.; Green, Russell A.; Upadhyaya, Sneha; Maurer, Brett W.; Yerro-Colom, Alba; Martin, Eileen R.; Cooper, Jon
Abstract: Multiple interbedded fine-grained layers in a sand deposit have a "smoothing" effect on the measured Cone Penetration Test (CPT) tip resistance ( q c ), resulting in a significant underestimation of the predicted liquefaction resistance of the sand layers. Trends identified by De Lange [14] through calibration chamber tests on stratified sand-clay profiles are used herein to develop a new thin-layer correction procedure for q c (the "Deltares" procedure). The efficacies of the Deltares and the independently-developed Boulanger and DeJong [6] procedures are both directly assessed using CPT data from calibration chamber tests and indirectly inferred from CPT-based liquefaction case histories in Christchurch, New Zealand. The results highlight limitations of the assessed thin-layer CPT q c correction procedures for layers less than 40 mm thick. Multiple, interbedded thin layers also influence the measured CPT sleeve friction ( f s ), but in a more complex way than they influence q c . To-date, no procedures have been proposed to address all the thin-layer-effects phenomena on the measured f s, with errors in properly characterizing the f s of a layer inherently influencing the accuracy of predicting the liquefaction susceptibility and potential of the layer. In totality, the thin-layer-effects correction procedures proposed to-date generally result in slightly less accurate predictions of the observed liquefaction severity for cases having highly stratified profiles, opposite of what would be expected and desired. Highlights: A new thin-layer effects correction procedure is developed from calibration chamber test data. The BD18 thin-layer correction procedure is assessed using calibration chamber data and field case histories. Current thin-layer correction procedures generally have limitations in correcting for layers less than 40 mm thick. Use of thin-layer correction procedures result in slightly less accurate predictions of observed liquefaction severity.